Analisis Pertumbuhan Ekonomi Dan Penetapan Sektor Unggulan Di Provinsi Jawa Timur Wilayah Timur Tahun 2010-2014 - Bambang Tri Wisnu Satria (Jurnal Ekonomi Pembangunan, 2016)
Title: "Analysis of the Economic Growth and Designation Sector Featured In East Java Province Eastern Region".The purpose of this research is: Knowing the pattern of economic growth in the district / city in East Java province eastern region, knowing what sectors be featured, flagship, prospectively, and lagging in district / city in East Java province east.The analytical methods used are: 1). Typology Analysis klassen2). AnalisaSLQ (Static Location Qoutient) and DLQ (Dynamic Location Qoutient), 3). Analysis GIS (Geographic information system).The results of the analysis using Klassen Typology analysis can be concluded that the pattern of economic growth and the District and City in the province of East Java East Region 4 Klassen typology classification of economic growth pattern that is region and Growing Fast Forward, Retarded, Fast Developing and Developed Depressed:Based on the analysis AnalisaSLQ (Static Location Qoutient) and DLQ (Dynamic Location Qoutient) and analysis of GIS (Geographic information system). Based on the value of SLQ and DLQ sectors that contributed most to the classification of Disadvantaged namely in Probolinggo to donate 11 (eleven) sector.